Effect of Diesel Engine Operating Conditions on the Particulate Size, Nanostructure and Oxidation Properties when Using Wasting Cooking Oil Biodiesel. (2015) - Man, X.J.; Cheung, C.S.; Ning, Z.
Abstract: Present work focuses on the effect of engine operating parameters, including the engine speed and engine load (air/fuel ratio), on the particulate nanostructure and oxidative reactivity when the engine is operated with WCO (waste cooking oil) biodiesel. The particulate samples were collected from the diluted exhaust produced by a medium-duty direct injection diesel engine and were used to analyze the physical and chemical properties via using the high-resolution transmission electron microscope (TEM) and the thermogravimetric analysis/differential scanning calorimetry (TGA/DSC). The TEM images reveal that larger primary particles are formed at low engine speed and high engine load. The particles with typical inner core-outer shell structure are common at high engine load due to the sufficiently high in-cylinder gas temperature and pressure. Quantitative analysis of the nanostructures indicates stronger effect in engine load than engine speed and more soot with shorter and more curving graphene layer at lower engine load. Furthermore, the results of TGA infer that the soot oxidative reactivity is closely related to the nanostructure and the effect of engine load at constant engine speed is more pronounced than the effect of engine speed.